La sensibilité photographique du géographe - Anaïs Marshall (EchoGéo)
For study territories, geographers Scientifics have various tools. The photographic approach has to be more considerate for the research perspectives offered. We can ask then if the photographic sensibility of the geographer is really allow an objective interpretation and a scientific analysis. To answer, six pictures of Peru have been first described and then analysed with the help of the fieldwork. Finally the geographer-photographer has to propose an objective picture, neutral and conform to the reality and easily interpreted by everyone.